Early Reading With Technological Pedagogical Content Knowledge (TPACK) Approach - Gifari Jakawali; Rahman (International Conference on Elementary Education, 2023)
Blended learning is a new challenge, especially for educators and students in the post-pandemic era. Educators are required to look for learning strategies that are interesting and innovative and facilitate students in learning activities at school. This study describes the TPACK approach's application in early reading activities in elementary schools with the help of modern technology-based learning media. This research uses the PTK method with the help of 4 stages: planning; implementation of class actions; observation/observation; and reflection, which was carried out for two cycles (meetings). Data was collected using an initial reading assessment instrument for one grade student at SD Negeri Pasirhuni 1 for the 2021/2022 academic year. The data was obtained in the form of formative test results from students. Samples used were first-grade elementary school students, totaling 13 students. Based on the results of the study, it is known that the TPACK approach is very significant in improving students' initial reading skills in elementary school.